2021
DOI: 10.4314/ijbcs.v15i3.22
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation et vulnérabilité des espèces végétales et stratégies d'adaptation des populations riveraines de la Forêt Classée du Kou (Burkina Faso)

Abstract: La problématique de la déforestation est importante dans les régions arides et semi-arides de l’Afrique. Les politiques de gestion des forêts excluant les besoins réels des populations font qu’elle persiste. Cette étude vise à améliorer la gestion participative et durable des forêts classées au Burkina Faso. Une enquête ethnobotanique impliquant 60 ménages des villages riverains de la Forêt Classée du Kou et un inventaire floristique sur 36 placettes ont été réalisés. L’indice de vulnérabilité des espèces a ét… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
(10 reference statements)
0
6
0
1
Order By: Relevance
“…For processing the survey data, we used the method used by Bériname et al (2018), Badjaré et al (2018) and Yaovi et al (2021). Thus, we calculated the citation frequency (F).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For processing the survey data, we used the method used by Bériname et al (2018), Badjaré et al (2018) and Yaovi et al (2021). Thus, we calculated the citation frequency (F).…”
Section: Discussionmentioning
confidence: 99%
“…Major parameters are taken into account for calculating the vulnerability index(Badjaré et al 2018;Yaovi et al 2021) …”
mentioning
confidence: 99%
“…This diversity is higher compared to other classified forests that have been inventoried in the same phytogeographical zone. Indeed, the floristic inventory carried out in the protected areas of Bala (Taïta, 1997), Bansié (Ouédraogo, 2004), Niangoloko (Ouoba, 2006), Pama (Mbayngone, 2008), Kou (Yaovi et al, 2021) and the two Balé (Tankoano, 2017) recorded respectively 282 species, 303 species, 353 species, 336 species, 206 species and 109 species. This difference reflects the importance of Péni Classified Forest (PCF) in the conservation of diversity despite its small size (1200 hectares).…”
Section: Discussionmentioning
confidence: 99%
“…The study revealed that local populations are aware of the decline and the disappearance of Detarium species from their habitat, primarily attributed to the overexploitation of plant parts, such as the bark and the trunk, alongside habitat destruction for agricultural expansion. This indiscriminate exploitation across all plant parts significantly jeopardises the species' survival (Yaovi et al, 2021). The major threats identified in Burkina Faso include bushfires, population growth, wood overexploitation and traditional mining exploitation.…”
Section: Local Perceptions Of Areas Of Abundance Threat Factors and T...mentioning
confidence: 99%
“…With increasing populations, NTFP market values have risen, putting greater pressure on these woody multipurpose species. This pressure contributes to the vulnerability of D. microcarpum and D. senegalense (Ouédraogo et al, 2021; Yaovi et al, 2021). In addition, the lack of effective management strategies and insecurity in West African Sahelian countries amplify the threats to these species (Zerbo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%